"They Planned Their Calendar… They Set Up Ready for What They Wanted to Feed the Tribe": A First-Stage Analysis of Narungga Fish Traps on Yorke Peninsula, South Australia. (2nd January 2016) - Roberts, Amy; Mollenmans, Adrian; Agius, Quenten; Graham, Fred; Newchurch, Jeffrey; Rigney, Lester-Irabinna; Sansbury, Fred; Sansbury, Lindsay; Turner, Peter; Wanganeen, Greg; Wanganeen, Klynton
ABSTRACT: This article outlines "first stage" research into Aboriginal fish traps located on Yorke Peninsula, South Australia. The project was undertaken by Flinders University researchers in collaboration with the Indigenous traditional owners of the region—the Narungga people. The research aimed to achieve a range of objectives including obtaining basic data as to the location and types of fish traps in the region as well as contextualizing these fish capture facilities in a variety of ways via traditional knowledge and contemporary perspectives, a consideration of temporal issues, a reflection on the role of traps in the Narungga coastal economy, and through reference to broader discussions (both nationally and internationally) concerning the timing and economic/socio-cultural importance of these technological innovations. Narungga knowledge systems and perspectives recorded in relation to the fish traps reveal multifaceted relationships between the community and their environment as well as associated religious/ritual engagement and cosmological knowledge. Comparison with neighboring areas reveals that the role of fish traps in coastal economies in the broader South Australia region is differential. Our observations also align with the conceptual approaches of prior researchers who have used fish traps to infer the existence or at least emergence of detailed socio-cultural organization in a late Holocene context.